Non-standard workers' perceptions of Malaysia’s social security programmes during the COVID-19 pandemic - Jaiyeoba, Haruna Babatunde; Fernando, Yudi; Moha Asri, Abdullah; Zuraidah, Mohd Sanusi (Penerbit Universiti Malaysia Pahang, 2024)
The emergence of the COVID-19 pandemic, along with its unprecedented economic and livelihood challenges, has had unparalleled repercussions on non-standard workers worldwide. To cushion the impact of COVID-19 on workers and employment, several measures were implemented by the Malaysian government. However, anecdotal evidence suggests that these measures largely focused on those in standard employment. Accordingly, this study explores non-standard workers’ perceptions of Malaysia’s social security programmes during the COVID-19 pandemic. The research adopts a qualitative design, with data collected from nine non-standard workers and analysed using thematic analysis. The results reveal that non-standard workers experienced job losses, financial strain, significant income reductions, and challenges in accessing government assistance during COVID-19. The findings also indicate that this group did not benefit as equally as standard workers from the government’s emergency social measures, such as wage subsidies, financial aid, and other pandemic-related programmes. While financial aid and special grants for micro-businesses provided short-term relief, many non-standard workers believe the government could have done more. Additionally, the government’s social security programmes were found to promote social cohesion and contribute to a more unified society. Overall, the findings underscore the need for inclusive and adaptable social security frameworks that address the unique needs of non-standard workers, particularly in times of crisis.